Leaf Area Index in Seedlings of Eucalyptus sp. - V. R. Andrade Neto; V. A. H. F. Santos; M. N. Garcia; R. A. Rodrigues; D. Franciskievicz; J. P. dos Santos (Scientific Electronic Archives, 2013)
Abstract: The aim of this study was to follow the development of leaf area index (LAI) of eucalyptus seedlings propagated through minicutting. The experiment was conducted in the greenhouse of the FLORA SINOP nursery with controlled conditions in order to ensure temperature around 30 C and relative humidity above 80%. The cuttings were collected from ministumps established in clonal minigarden and were prepared in tubes with substrate. The leaf area index was determined with the aid of an integrator of leaf area and after obtaining the results were evaluated by analysis of variance (f = 0.05) and Tukey test at 5% probability. The Clone 1 and Clone 2 were the only ones to present frank leaf area development under conditions of the greenhouse, while the others came to increase, significantly, the values of leaf area only in sunny conditions. The Clone 4 had a different behavior from the others when it was in sunny conditions, since his leaf area decreases due to abscission of some leaves under these conditions. The results showed different behaviors between the clones tested with regard the expansion of leaf area during the analysis period. Keywords: cuttings, eucalyptus, clone